The Genesis of Crisis Communication in Twitter: from Witnesses to Gatewatchers - Rossi, Luca; Zurovac, Elisabetta (AoIR Selected Papers of Internet Research, 2013)
During crisis events individuals look for information and try to share useful content or testify their own experience through social media. The research for valuable information is, relies largely on information provided by news agencies and official actors. This collective behavior leads, on a given amount of time, toward the emergence of gatewatching activities where digital media are used to reshare and to control information. This paper will investigate how this phenomenon emerge looking at the Twitter conversations produced during the first five hours after the earthquake that struck Emilia Romagna region in Italy on May 20th 2012. We have been able to detect, in the early user-led phase of the phenomenon, what kind of messages were produced and how user-produced communication results in different network structures.